2017
DOI: 10.1177/1078155217692400
|View full text |Cite
|
Sign up to set email alerts
|

Potential cost savings by dose down-rounding of monoclonal antibodies in a community cancer center

Abstract: Purpose Increasing new cancer cases and approval of effective but expensive new drugs extending survival have led to unsustainable cancer care costs. Potential cost savings by a hypothetical dose down-rounding project of monoclonal antibodies at a community-based cancer center is presented. Methods From October 2014 through October 2015, metastatic cancer patients receiving monoclonal antibodies at CHI-Health St Francis Cancer Treatment Center in Grand Island, Nebraska, were identified through electronic healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…16 Many studies have calculated wastage and costs for multiple expensive drugs, instead of performing an in-depth review of a single drug. 1721 Some studies have examined a single drug’s retrospective usage data to explore cost-saving strategies including dose rounding, vial sharing, and estimating the ideal vial size; however, wastage data were not analysed. 2224 Other studies have made extrapolations from short data collection periods, instead of making calculations from all patient-level data.…”
Section: Introductionmentioning
confidence: 99%
“…16 Many studies have calculated wastage and costs for multiple expensive drugs, instead of performing an in-depth review of a single drug. 1721 Some studies have examined a single drug’s retrospective usage data to explore cost-saving strategies including dose rounding, vial sharing, and estimating the ideal vial size; however, wastage data were not analysed. 2224 Other studies have made extrapolations from short data collection periods, instead of making calculations from all patient-level data.…”
Section: Introductionmentioning
confidence: 99%
“…In one community cancer center, projected annual savings of rounding to the nearest vial size of 11 monoclonal antibodies reduced costs by $220,793.80 if rounded by 5% and $454,461.10 by 10% per year. 7 In another analysis, cost savings of dose rounding seven biological agents (total of 126 doses) within 10% to the nearest vial size over a three-month period in an inpatient pharmacy was $124,434, which results in $497,736 saved annually. 5 An analysis investigating the benefits of using biosimilars found that their use reduced costs by about 40% compared with the reference product.…”
Section: Discussionmentioning
confidence: 99%
“…Rounding of drug doses to the nearest vial size when the difference is within 5% to 10% of the prescribed dose is an initiative employed by many institutions in order to reduce drug waste and cost. [4][5][6][7] The same measure is supported by the Hematology/Oncology Pharmacy Association and endorsed by the National Comprehensive Cancer Network. 6 Utilization of biosimilars in place of reference products is an additional approach to reduce the cost of oncology care.…”
Section: Introductionmentioning
confidence: 99%
“…This packaging of expensive infused drugs in quantities larger than needed is the cause of the wastage of medicines [19]. In this regard, it has been said that a Dose Rounding and Cost Reduction of Anticancer Agents policy implementation targeting the reduction of wastage may substantially reduce the expenditure on pharmacies and provide cost-benefit [18].…”
Section: Introductionmentioning
confidence: 99%
“…As per the report published in 2009 by the Canadian Cancer Society, newer anticancer drugs cost around 65,000 Canadian Dollars per course of treatment [17]. Apart from spending on research, a reason for the high cost of cancer treatment can be attributed to drug wastage [18]. The international guideline allows doses to be rounded (banded) for 5–10%.…”
Section: Introductionmentioning
confidence: 99%